PENDIDIKAN HUKUM DI ERA TRANSISI DALAM NEGARA DEMOKRASI MENUJU INDONESIA BARU - Khaidir Anwar (Faculty of Law, Universitas Diponegoro, 2011)
The Higher Law Education was started from senior high school level (Rechsschool), founded in 1908 during the Dutch colonial occupation. In 1924, law education was upgraded to university level which was called as